COOPERATION BETWEEN INDONESIA – SINGAPORE DEVELOPING FUNTASY ISLAND IN BATAM ISLAND - Dheastine Febriany Gea; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Indonesia is a country that entered into the Southeast Asia region and can be seen also that Batam Island is a neighboring city also directly adjacent to Singapore and Malaysia. Because of the very strategic location that makes Batam is in international shipping lane, thus making Batam cooperate with Singapore in developing “Funtasy Island” to support the tourism potential. Tourism activity is one of the sectors that play a role in the process of development and development of the region, namely in giving a contribution that directly affects the economy of the country itself. “Funtasy Island” is a resort project that will be one of the tourist destinations located on Manis Island in the waters of the Riau Islands. This island will then be converted into the largest eco-theme park concept in the world. So this big project was created and developed through the collaboration of two companies from both countries, namely Indonesia and Singapore.This study uses qualitative research methods with descriptive analytical models, where the purpose of this study is to describe the facts and characteristics of certain population areas in a systematic, factual, and accurate manner. This study uses secondary data collection techniques and primary data, then connects the theory with data obtained through library research. Secondary data can be obtained from books, journals, government reports, documents, magazines, websites, and other sources. For primary data, the authors conducted a field study in collecting data needed for this study. And the theoretical framework used to explain the problem in this study is the International Perspective theory, the perspective of Liberalism.With the MoU on cooperation between countries, the signing of Special Economic Zones, as well as promotional activities carried out by the two countries showed that the economic development of Batam Island in collaboration with Singapore could be said to be good and beneficial for both countries. Because with the "Funtasy Island" project, it will increase regional and foreign exchange income, which can encourage the development of Indonesia's economy, including Batam Island.Keyword: cooperation, liberalism, tourism, relations.